Making the supreme court : The politics of appointments, 1930-2020 - Cameron, Charles M.; Kastellec, Jonathan P. (New York : Oxford University Press, 2023)
Appointments to the United States Supreme Court are now central events in American political life. Every vacancy unleashes a bitter struggle between Republicans and Democrats over nominees; and once the seat is filled, new justices typically vote in predictable ways. However, this has not always been the case. As late as the middle of the twentieth century, presidents invested little time and effort in finding and vetting nominees, often selecting personal cronies, who senators briskly confirmed. Media coverage was desultory, public opinion was largely non-existent, and the justices often voted independently and erratically.
Keywords: Law/ New politics/ New justice/ New Policies